ANALYSIS THE KINDS AND COMPOSITIONS OF RADIOISOTOPE ELEMENT WITHIN THE MINE SAMPLES BY MCA SPECTROMETRY IN WEST TIMOR ISLAND NUSA TENGGARA TIMUR - Pasangka, Bartholomeus; -, Prayoto; Brotopuspito, Kirbani Sri; -, Waluyo (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
The problems analyzed in the research are the kinds and compositions of radioisotope within the mining substance in the West Timor Island. The purposes of the research : 1) to investigate and determine the kinds of radioisotope elements in the mining substance, 2) to determine the radiation energy, counts, half life, and percentage of radioisotope element deposit within the mining substance. The methods of the research include observation, survey, sampling, spectrometry, analysis, and interpretation. On the observation, survey, and sampling steps, the 50 samples taken are distributed at the survey location. Those samples are analyzed with the several steps including: to dry the samples, to refine, to burn until temperature 800o C, to stabilize and dry again. All samples are analyzed with spectrometry system on the multi-channel analyzer (MCA) that can separate element of the samples. The results obtained are that the kinds of radioisotope element deposit within the samples of mining substance consist of Actinium series component and other association elements, also energy radiation, counts, half life, and percentage of radioisotope element deposit within the mining substance respectively revolved between 26.6 keV to 1562.3 keV,1 cps to 24867cps, 3.16 minutes to 1.405 x 1010 years, and 0.19% to 99.00%. The main elements on Actinium series within the samples of mining substance comprise of U-235, Th-231, Pa-231, Th-227, Bi-211, and Rn-219, and other isotopes Bi-212, Th-232, Pb-212, Pa-234, Ac-228, Ra-226, and Pb-214, with energy radiation, counts, half life, and percentage of radioisotope element deposit respectively revolved between 26.6 keV to 426.9 keV, 1 cps to 24867 cps, 7.038 x 108 years to 1.405 x 1010 years, and 1.0% to 18.7 %. The association elements consist of Am-241, Cs-134, Cs-136, Cs-138, Ce-141, Ce-144, Ba-133, Ba-140, Cd-109, Se-75, Te-132, Co-57, Mo-99, Fe-59, Kr-85, Kr-88, Kr-89, Sb-122, Sb-124, Sb-125, Xe-125, Xe-131m, Xe-133m, Xe-135, Xe-135m, Xe-138, I-124, I-125, I-130, I-131, I-132, I-134, I135, Br-82, Y-91m, Y-92, Y-93, Y-94, W-187, Sr-91, Sr-92, Sr-93, Zr-97, Rb-89, Rh-105, Ni-65, Sn-133, Be-7, Nb-94, Nb-96, Nb-97, Ag-110m, As,76, Cr-51, Eu-152, and Tc-96.